Familial corpus callosum agenesis - Özdirim, Emire; Renda, Yavuz (The Turkish Journal of Pediatrics, 1978)
Three siblings with agenesis of Corpus Callosum were described. Their chief complaints were motor weakness, mental retardation and spasticity which were more obvious after three months of age. Physical examination showed primary optic atrophy, increased muscle tones, spasticity, and mental and motor retardation. Pneumoencephalograms showed increased ventricular size, widening of the interventricular space and cortical atrophy. EEG’s were disturbed generally. An autosomal recessive type of inheritance was accepted as the mode of inheritance.